Predictive models of cardiovascular complications of hypertension - Longa Ortiz, Karen Roxana (2025)
Introduction: The predictors of cardiovascular complications of hypertension can be diverse, highlighting older age, precarious social, economic and personal conditions, as well as body conditions, susceptible to modification with comprehensive health interventions. Objective: To predict cardiovascular complications of hypertension in users of a Peruvian public hospital using models. Methodology: The research was analytical, predictive, cross-sectional, with retrospective data collection. 303 patients who attended the Cajamarca Regional Hospital during 2022 were investigated. Sociodemographic data and data on cardiovascular complications of hypertension were obtained from the data stored by the hospital. Descriptive statistics included absolute and relative frequencies, confidence intervals, mean and dispersion measures, and predictive models were performed using binary logistic regression and Cohen's Kappa Index, with a statistical significance of p<0.05. Results: The most frequent cardiovascular complication was heart failure (49.5%). The model for heart failure predicts 70.6% and the years of diagnosis, occupation and marital status are included in the equation, for atrial fibrillation it predicts 82.2% and the equation includes age, sex, years of diagnosis, level of education and marital status and for angina pectoris it predicts 84.8% and the equation includes age, sex and years of diagnosis. Conclusions: The models created for the cardiovascular complications of hypertension have good predictive capacity, therefore, accurate and efficient performance in the predictor variables will allow favorable control of the complications of the disease.